Mechanosensitive transient receptor potential vanilloid 4 regulates Dermatophagoides farinae–induced airway remodeling via 2 distinct pathways modulating matrix synthesis and degradation. Issue 4 (10th January 2017) - Gombedza, Farai; Kondeti, Vinay; Al‐Azzam, Nosayba; Koppes, Stephanie; Duah, Ernest; Patil, Prachi; Hexter, Madison; Phillips, Daniel; Thodeti, Charles K.; Paruchuri, Sailaja
Abstract : Contributions of mechanical signals to airway remodeling during asthma are poorly understood. Transient receptor potential vanilloid 4 (TRPV4), a mechanosensitive ion channel, has been implicated in cardiac and pulmonary fibrosis; however, its role in asthma remains elusive. Employing a Dermatophagoides farinae– induced asthma model, we report here that TRPV4‐knockout mice were protected from D. farinae– induced airway remodeling. Furthermore, lung fibroblasts that were isolated from TRPV4‐knockout mice showed diminished differentiation potential compared with wild‐type mice. Fibroblasts from asthmatic lung exhibited increased TRPV4 activity and enhanced differentiation potential compared with normal human lung fibroblasts. Of interest, TGF‐β1 treatment enhanced TRPV4 activation in a PI3K‐dependent manner in normal human lung fibroblasts in vitro . Mechanistically, TRPV4 modulated matrix remodeling in the lung via 2 distinct but dependent pathways: one enhances matrix deposition by fibrotic gene activation, whereas the other slows down matrix degradation by increased plasminogen activator inhibitor 1. Of importance, both pathways are regulated by Rho/myocardin‐related transcription factor‐A and contribute to fibroblast differentiation and matrix remodeling in the lung. Thus, our results support a unique role for TRPV4 in D. farinae– induced airway remodeling and warrant further studies in humans for it to be used as a novel therapeutic target in the treatment of asthma. —Gombedza, F., Kondeti, V., Al‐Azzam, N., Koppes, S., Duah, E., Patil, P., Hexter, M., Phillips, D., Thodeti, C. K., Paruchuri, S. Mechanosensitive transient receptor potential vanilloid 4 regulates Dermatophagoides farinae– induced airway remodeling via 2 distinct pathways modulating matrix synthesis and degradation. FASEB J . 31, 1556–1570 (2017) www.fasebj.org